AN ANALYSIS OF VIEWERS’ RECEPTION ON THE VIDEO MESSAGE “ SAYA MUALAF BILA” ON DEDDY CORBUZIER YOUTUBE CHANNEL - Diana Wahyuni; Yanto Yanto; Sri Narti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Youtube is one part of social networking that can create a very close interaction and communication relationship between its users. Inside the YouTube social media account, the account is created by people who basically want to be a part of YouTube content creators. Many people out there who like to play Youtube but do not have the channel account. YouTube channel accounts are made with a variety of content, there are accounts that specialize in making videos of one's daily life, specialist accounts for opinion videos related to issues that are currently hot, specialist accounts for motivational videos, specialist accounts for culinary videos, specialist accounts for videos prank videos and more. What will be the focus of the researcher in this study is the video titled